2018
DOI: 10.1186/s13071-017-2590-x
|View full text |Cite
|
Sign up to set email alerts
|

Habitat properties are key drivers of Borrelia burgdorferi (s.l.) prevalence in Ixodes ricinus populations of deciduous forest fragments

Abstract: BackgroundThe tick Ixodes ricinus has considerable impact on the health of humans and other terrestrial animals because it transmits several tick-borne pathogens (TBPs) such as B. burgdorferi (sensu lato), which causes Lyme borreliosis (LB). Small forest patches of agricultural landscapes provide many ecosystem services and also the disservice of LB risk. Biotic interactions and environmental filtering shape tick host communities distinctively between specific regions of Europe, which makes evaluating the dilu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 92 publications
2
52
0
Order By: Relevance
“…The distribution and diversity of pathogens in sheep may be attributed to the difference in macroclimate, tick species, tickdwelling habitat, and landscape between districts. Particularly, questing ticks can be found in habitats like herb layer and vegetation (41,42). In XUAR, cattle, horses, and sheep often co-feed in the same district, and there are also many small mammals in areas with high vegetation (43).…”
Section: Resultsmentioning
confidence: 99%
“…The distribution and diversity of pathogens in sheep may be attributed to the difference in macroclimate, tick species, tickdwelling habitat, and landscape between districts. Particularly, questing ticks can be found in habitats like herb layer and vegetation (41,42). In XUAR, cattle, horses, and sheep often co-feed in the same district, and there are also many small mammals in areas with high vegetation (43).…”
Section: Resultsmentioning
confidence: 99%
“…For example, a recent study has found that ecotonal habitat and edge density affect B. burgdorferi ( s.l. ) prevalence in European forest fragments [ 51 ]. Surveys from England so far suggest that the dominant genospecies present are the bird-associated genospecies B. garinii and B. valaisiana with B. afzelii and B. burgdorferi ( s.s. ) being apparently absent from many sites [ 52 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, landscape structure and connectivity as well as host abundance and diversity may also play a role in the establishment of ticks in forest habitats. It had been shown that I. scapularis (and its western counterpart I. pacificus) is predominantly found in woodlands with high canopy cover compared to open shrublands, yet, on the other hand forest fragmentation contributes to higher prevalence of B. burgdorferi along forest edges and urban forests [22,54,55]. It is currently unclear how landscape structure affects the colonization ability of I. scapularis and why regions like Algonquin Park, with very dense mixed forests, show a lower suitability for ticks.…”
Section: Plos Onementioning
confidence: 99%